MODEL PENGEMBANGAN KREATIVITAS ANAK MELALUI PEMBELAJARAN SENI BUDAYA BERBASIS MUSIK RIAU BAGI SISWA SEKOLAH DASAR KELAS ATAS - Zufriady Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
Competency of primary school teachers in teaching low SBK can not increase the creativity of students. When viewed from the musical wealth of Riau which are many and varied, lessons should SBK can be done well. It is not so considered by the art educators and is the background for the model-based development of student creativity Riau music performed by R & D through the stages of survey, design models, testing, and validation. The use of this model can enhance students' creativity as the ability to develop rhythm, choose the color of the instrument, tool making, composing music, and composing music grooves. This model also helps the teacher in the learning process and simultaneously lift Riau music. SBK learning can enhance students' creativity and preserve the values of social, educational, religious, and human values contained in Riau music, if teachers can perform well. Instead of learning SBK who have not yet developed the art of Riau tradition as a foundation for creative, cultural roots will gradually disappear.